WATER DEMAND AND TECHNICAL-ECONOMIC VIABILITY OF COWPEA GROWN IN DIFFERENT PRODUCTION SCENARIOS (Nativa, 2024)
ABSTRACT: Water demand and agronomic and economic efficiency of cowpea are strongly related to agricultural practices and climatic conditions. This study aimed to determine in which cropping season cowpea has the highest water demand and maximum agronomic and economic efficiency as a function of water stress under the edaphoclimatic conditions of the semi-arid region of northeastern Brazil. Cowpea was cultivated in two cropping seasons (rainy and dry) and subjected to five forms of water stress (without water stress, water suspension for 5, 10 and 15 days and rainfed cultivation) and four replicates, started in the flowering and grain filling stages, under no-tillage system. Agronomic (yield, biomass, harvest index and water use efficiency) and economic (gross revenue, net revenue, rate of return and profit margin) parameters were evaluated. The water demand of cowpea in the dry season was 20.2% higher than in the rainy season; consequently, the Kc values obtained were also higher in this period. The climatic conditions that occurred during the cropping seasons and water stress negatively influenced the agronomic performance and financial profitability of cowpea, being more evident in the rainfed cultivation. For the edaphoclimatic conditions of the study, cowpea can be grown without significant losses of yield and profitability in both cropping seasons, provided that the water stress does not last more than 10 days during its reproductive stage.Keywords: profitability; Vigna unguiculata; water stress; cropping season Demanda hídrica e viabilidade técnico-econômica do feijão-caupi cultivado em diferentes cenários produtivos RESUMO - A demanda hídrica e a eficiência agronômica e econômica do feijão-caupi estão fortemente relacionados com as práticas agrícolas e a condições climáticas. Este trabalho teve como objetivo determinar em qual época de cultivo o feijão-caupi apresenta maior demanda hídrica e máxima eficiência agronômica e econômica em função do estresse hídrico, nas condições edafoclimáticas da região semiárida do nordeste do Brasil. O feijão-caupi foi cultivado em dois períodos de cultivo (chuvoso e seco) e submetido a cinco formas de estresse hídrico (sem estresse hídrico, suspensão de água de 5, 10 e 15 dias e plantio de sequeiro) com quatro repetições, iniciado nas fases de floração e enchimento de grãos, em sistema de plantio direto. Foram avaliados parâmetros agronômicos (produtividade, biomassa, índice de colheita e eficiência do uso da água) e econômicos (renda bruta, renda líquida, taxa de retorno e margem de lucro). A demanda hídrica do feijão-caupi no período seco foi 20,2% superior a do período chuvoso, consequentemente, os valores de Kc obtidos também foram superiores nesse período. As condições climáticas ocorridas nos períodos de cultivos e o estresse hídrico influenciaram negativamente no desempenho agronômico e rentabilidade financeira do feijão-caupi, sendo mais evidenciada no cultivo de sequeiro. Para as condições edafoclimáticas do estudo, o feijão-caupi pode ser cultivado sem significativas perdas de produtividade e rentabilidade em ambos os períodos de cultivo, desde que o estresse hídrico não seja superior a 10 dias durante sua fase reprodutiva.Palavras-chave: rentabilidade; Vigna unguiculata; estresse hídrico; época de cultivo.